Dispersion of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) in kale and cabbage fields - Da Silva Ponce, Franciely [UNESP]; De Oliveira, Moisés Daniel [UNESP]; De Lima Toledo, Claudia Aparecida [UNESP]; De Oliveira, Lucas Alves [UNESP]; Da Silva, William Ricardo Monesi; Júnior, Santino Seabra; De Oliveira, Regiane Cristina [UNESP] (Lepidus Tecnologia, 2022)
Parasitoids belonging to Trichogramma are utilized for pest management worldwide. The dispersal ability of these insects in crops determines the number of release points necessary for satisfactory results in terms of parasitism and consequently, pest management. To determine the dispersal capacity of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) in kale and cabbage crops, a 26 × 26 m area was demarcated, in which cards containing Anagasta kuehniella eggs were distributed in a concentric and equidistant manner. At the center of each area, 100,000 parasitoids were released and parasitism was allowed for 24 h. The experimental design was completely randomized, with five treatments (distance) and four replications. The average dispersal distance was 6.27 m in kale and 6.07 m in cabbage, whereas the dispersal area was 81.23 m2in kale and 79.03 m2in cabbage, thus determining 123 and 126 release points for kale and cabbage, respectively.
Keywords: Biological control program; Brassica oleracea; integrated pest management; inundative release